Kingdom of Swaziland : 2010 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Swaziland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Swaziland economy continues to underperform, reflecting the impact of the global economic crisis. The impact of the crisis has been felt mostly in revenue transfers of the Southern African Customs Union (SACU) to Swaziland. Executive Directors welcomed Fiscal Adjustment Roadmap (FAR), which focused on restoring fiscal sustainability, improving competitiveness, and strengthening financial supervision. They noted that key challenges are restoring fiscal sustainability, addressing HIV/AIDS, reducing poverty, and creating employment. Directors emphasized the need for fiscal adjustment and budgetary reforms. Directors noted that the banking system remains in good health.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet